A propaganda institucional como estratégia de valorização da imagem empresarial da Pirahy Alimentos - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This final paper studied the importance of institutional advertising as corporate image enhancement strategy. As empirical object, we choose the Pirahy Alimentos, highlighted in the rice sector, located in São Borja, western border of the state of Rio Grande do Sul. The used methodology was qualitative research and semi-structured interview with the communication team of the analyzed company. The analytical chapters sought to understand the importance of a company image valuation and what the advantages of his managing, focusing our attention on institutional advertising as a recovery tool of the studied image. Tried also point out the positive elements of a corporate video, as well as possible relationships with the corporate image and finally, analyze the process of planning, appropriation and transmission of a institutional video from Pirahy Alimentos company. As a final result, we understand that institutional advertising is a powerful image recovery strategy, through it, the company can be closer to the audiences, showing its values and differential, we also identified how important is the presence of public relations professionals for the development of these tasks, although there is strong competition with the marketing professionals, a fair dispute considering the importance of both areas. We also understand that the communication strategy is more efficient in a set, that is, not just a corporate video or a website are sufficient for the image management of a company, but the use of multiple contact Public combinations.
Keywords: Propaganda; Comunicação empresarial; Pirahy Alimentos Ltda; Marketing institucional; Business Communication; Institutional Marketing; CNPQ::CIENCIAS SOCIAIS APLICADAS